1999
DOI: 10.1007/s000110050417
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic histamine, growth rate, plasma prolactin and growth hormone levels in rats with long-term portacaval anastomosis

Abstract: We suggest that increased histaminergic activity in the hypothalamus may be involved in the development of growth retardation and in the enhanced basal secretion of prolactin in male rats with long-term PCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…38 Portacaval surgery results in a significant weight loss immediately after the procedure. However, 1 month after surgery, the weight-gain curves are re-established, 7 and at 6 months, the time at which the animals in the present study were killed, the total food intake and the weight-gain curves are normal. 7,8 It is therefore unlikely that the histamine receptor changes in the present study were a result of feeding problems.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…38 Portacaval surgery results in a significant weight loss immediately after the procedure. However, 1 month after surgery, the weight-gain curves are re-established, 7 and at 6 months, the time at which the animals in the present study were killed, the total food intake and the weight-gain curves are normal. 7,8 It is therefore unlikely that the histamine receptor changes in the present study were a result of feeding problems.…”
Section: Discussionmentioning
confidence: 55%
“…[6][7][8] Relating the functions controlled by histamine to the clinical presentation of HE, it appears a priori that histamine could participate in the pathogenesis of the sleep disturbances, decreased spontaneous voluntary movement, and increased plasma prolactin levels in patients with HE and in the hormonal changes, growth retardation, and the altered vigilance, locomotor activity, and circadian rhythmicity in rats with PCA. Consistent with these possibilities, we have previously shown that blockade of central histamine H 1 receptors with the specific antagonist, pyrilamine (mepyramine), restores the altered circadian rhythmicity of feeding and locomotor activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously suggested that histaminergic synaptic imbalance may have contributed to the sleep disturbances in rats with PCA. 18 We have now examined the effects of histamine H 1 receptor blockade on feeding, locomotor activity, and circadian rhythmicity in rats with long-term PCA to find out whether the modified histaminergic neurotransmission in the brain of rats with portacaval anastomosis 6 months after surgery 12,[16][17][18] has also participated in the generation and maintenance of the disturbances in the circadian rhythmicity of feeding and locomotor activity. Pyrilamine (mepyramine), a selective and high-affinity H 1 receptor antagonist, 29 was used to block histamine H 1 receptors in the CNS.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10] These rats also have disturbances in their food intake 11 and show marked growth retardation. 12 Although much research has been performed to elucidate the pathophysiological background of PSE, the exact mechanisms that underlie this condition are still largely unclear. PSE has been described as a disorder of multiple neurotransmitter systems.…”
mentioning
confidence: 99%